The Effect of Capital and Personnel Expenditures on the Level of Regional Financial Autonomy in Yogyakarta - Nafisya, Aliyana Salma; Faiz, Ihda Arifin (AKUMULASI: Indonesian Journal of Applied Accounting and Finance, 2024)
Yogyakarta has high spending on capital and personnel expenditures, with the regional financial dependency rate remaining high. This study investigates the impact of capital and personnel expenditures on Yogyakarta's level of regional financial autonomy. This study utilized a quantitative method and analyzed data from all regencies and cities in Yogyakarta between 2015 and 2022. A total of 40 observations were based on a purposive sampling approach and examined using linear regression. The findings indicate that both variables have a significant negative impact on the level of regional financial autonomy. The study results can guide future financial management strategies for the regional government. In addition, this study contributes to the understanding of regional financial autonomy characteristics, particularly in Yogyakarta.